(untitled) (Research, Society and Development, 2020)
Breastfeeding contains all the necessary nutrients for the newborn and should be the only food offered to the child up to six months of age, in view of the benefits provided by this practice. This study aimed to identify, in the scientific literature, publications on the guidelines that are provided to mothers during hospital discharge by professional nurses. This is a descriptive, literature review, integrative research, according to Cooper. Data collection took place from February to April 2020, guided by the following question: is the guidance on breastfeeding at hospital discharge happening and how does it happen? The data were analyzed by themes as proposed by Bardin. The main results showed that the majority of puerperal women are not receiving the guidelines as recommended and, when received, are not sufficient to meet the demands presented. We conclude that the participation of nursing in delivery and hospital discharge is important, offering the necessary support for the puerperal woman with empathy and qualified services, thus minimizing early weaning.